Navigation and Positioning Methods Using Signal of Opportunity of Low Earth Orbit Satellites - ZHANG Yichao; ZHAO Xiangtian; ZHAO Yafei; SUN Yaohua; JIANG Cheng; ZHANG Shijie; PENG Mugen (天地一体化信息网络)
In recent years, low earth orbit (LEO) giant constellations have developed rapidly, and their main goal is to provide users with high-speed Internet services. As a global coverage satellite communication system, its potential in navigation, positioning and time service remains to be developed. LEO constellations have the advantages of high signal landing power, abundant signal resources, and high survivability. Utilizing the signal of opportunity of LEO satellites for positioning is a backup navigation method when GNSS is unavailable. This paper provided a detailed summary of the deployment, signal and frequency characteristics of typical LEO constellations worldwide, and outlined the methods of receiving and processing LEO satellite signals and positioning solutions. A mathematical simulation was conducted on the opportunistic navigation method of LEO satellites, and Doppler positioning and pseudorange positioning methods were compared and analyzed. The future development trend of opportunistic navigation of LEO satellites was discussed.